Abundance and distribution of microplastics and persistent organic pollutants in selected rivers of Peninsular Malaysia / Norkhairiyah Anuar - Norkhairiyah , Anuar (2020)
Nearly 70 to 80 percent of microplastics are believed to be transported to the sea through rivers. Yet, less attention has been given to the accumulation of microplastics in the freshwater environment. They are emerging anthropogenic contaminants on account of their potential to adsorb and/or release POPs from and/or to the surrounding environment, and become the vector transferring these pollutants from water to the food web. This study is aimed to explore the abundance and distribution of microplastics and POPs in six rivers of Peninsular Malaysia, which comprised of three rivers from the West Coast (Sepetang River, Serkam River, and Ayer Masin River) and three rivers from the East Coast (Sedili Besar River, Cherating River, and Semerak River). The objectives of this research are to identify the anthropogenic activities that may contribute to the generation of microplastics and POPs, to investigate the abundance and distribution of microplastics, to determine the concentrations of POPs, and, to analyze the relationship between the microplastics abundance, POPs concentration and anthropogenic activities along these rivers. Eight sites were established along each river to ensure maximum coverage of the rivers studied, while anthropogenic activities were investigated through observation of 5 km radius along each river. River sediment samples were collected using shovel, while plankton nets were utilized to capture microplastics in river water. Density separation was conducted to extract microplastics in the sediment, using concentrated NaCl solution followed by wet sieving through a set of Tyler Sieves. Identification of microplastics was conducted based on morphological characteristics (i.e. type, size and colour). As for POPs identification, Liquid-liquid Extraction and Soxhlet Extraction were performed, followed by GC-MS/MS analysis. Sepetang River, Cherating River, and Ayer Masin River substantially demonstrated greater number of anthropogenic activities, characterized as the hotspots of anthropogenic activities, followed by Sedili Besar River, Serkam River and Semerak River. Correspondingly, the highest prevalence of microplastics abundance in river sediment was discovered in Sepetang River with an average abundance of 101.39 ± 54.69 particles/kg, while in river water, Ayer Masin River had the greatest number of microplastics with average abundance of 0.0101 ± 0.0052 particles/m3. Majority of the microplastics were films and white in colour, with a dominant size fractions of 1.0 to 5.0 mm in river sediment, and 0.1 to 0.5 mm in river water. 1,2-Benzenedicarboxylic acid, diisooctyl ester (DIOP), which are generally grouped in Phthalate esters (PAEs), was the dominant POPs identified. The highest concentration of POPs in river sediment was observed in Sedili Besar River (677.49 ppm), while the highest concentration in river water was recorded in Cherating River (153.41 ppm). Generally, it can be said that the problem of microplastics and POPs pollution rooted in the prevailing production and consumption pattern of plastic materials, on grounds of great contributions from various anthropogenic activities. Correlation study revealed no relationship between the abundance of microplastics and POPs concentrations in rivers of Peninsular Malaysia. Overall, the results of this study could provide valuable background information for microplastics and POPs pollution in selected rivers of Peninsular Malaysia.